Enhancing skd readiness in peripheral regions: A visual-digital approach and public speaking pedagogy to achieve performance equity in kupang city - Adellia Agusta; Noverius Henutesa Nggili; Roidah Afro; Sirilus N. M. Lelan; Mariano A.T. Nugraha; Yuan Valentino Elim; Dalmasius Naif; Aprianus Ronny Paskal Modena; Descorina Priscilla Br Sitompul (Al Qodiri : Jurnal Pendidikan, Sosial dan Keagamaan, 2026)
Persistent educational inequality in peripheral regions continues to undermine students’ competitiveness in high-stakes standardized assessments, particularly when instructional practices remain misaligned with the cognitive and affective demands of such tests. Addressing this gap, this study investigates the effectiveness of an integrated visual-digital and public speaking pedagogical model in enhancing students’ readiness for the Basic Competency Test (SKD) in Kupang City, Indonesia. Employing a mixed-methods quasi-experimental design with a pretest–posttest structure, the study involved 60 senior high school students selected through purposive sampling. The intervention combined multimedia-based instruction to strengthen analytical reasoning and general knowledge with public speaking training to develop confidence and situational judgment. Quantitative analysis using paired sample t-tests and effect size measures revealed statistically significant improvements across all domains, with large effects observed in cognitive outcomes and moderate yet meaningful gains in affective competencies. Qualitative findings further indicated increased engagement, motivation, and active participation as key mechanisms underlying these improvements. Importantly, the results demonstrate that pedagogical integration exerts a more decisive influence on learning outcomes than technological infrastructure alone, challenging dominant assumptions in digital education discourse. The study advances a novel dual-domain learning framework that explicitly integrates cognitive processing and affective readiness as interdependent drivers of performance. From a practical standpoint, the findings offer a scalable and context-sensitive instructional model for underserved regions. Ultimately, this research argues that achieving educational equity requires not merely expanding access to technology, but fundamentally reconfiguring pedagogy to align with the holistic learning needs of students in resource-constrained environments.